2013
DOI: 10.1787/5k4bw6kg6ws2-en
|View full text |Cite
|
Sign up to set email alerts
|

Trade Facilitation Indicators

Abstract: The OECD Trade Policy Paper series is designed to make available to a wide readership selected studies by OECD staff or by outside consultants. This series continues that originally entitled OECD Trade Policy Working Papers. This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 5 publications
0
24
0
2
Order By: Relevance
“…15 While not specifically targeted at describing the Internet's impact, evidence from the OECD's work on trade facilitation clearly shows the positive effect of the Internet on trade. This work estimated the impact of addressing specific hurdles in the trade and border procedures in 107 countries at various stages of development (Moïsé and Sorescu, 2013). It found that measures to harmonise and simplify documents, and to use automated processes could reduce trade costs for low income countries by 3% and 2.3% respectively.…”
Section: The Internet and Tradementioning
confidence: 99%
“…15 While not specifically targeted at describing the Internet's impact, evidence from the OECD's work on trade facilitation clearly shows the positive effect of the Internet on trade. This work estimated the impact of addressing specific hurdles in the trade and border procedures in 107 countries at various stages of development (Moïsé and Sorescu, 2013). It found that measures to harmonise and simplify documents, and to use automated processes could reduce trade costs for low income countries by 3% and 2.3% respectively.…”
Section: The Internet and Tradementioning
confidence: 99%
“…They found that formalities -procedures indicator accounts for 5.4% of potential trade cost savings, indicator advance rulings for 3.7%, indicator formalities -automation for 2.7%, and indicator fees and charges for 1.7%. Moïsé and Sorescu (2013) suggested that greatest impact on trade volumes and trade costs have the indicators related to the availability of trade-related information, the simplification and harmonization of documents, the streamlining of procedures and the use of automated processes. They found that the combined effect of improvements in these areas is greater than the simple sum of the impact of individual measures, reaching almost 14.5% reduction of total trade costs for low income countries, 15.5% for lower middle income countries and 13.2% for upper middle-income countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We use the OECD data base for the values of the Trade facilitation indicators for these countries and apply them in augmented gravity trade model to estimate their impact on bilateral trade flows according to Moïsé and Sorescu (2013). We follow Moïsé and Sorescu (2013) and apply the same model to this subset of countries…”
Section: Research Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…These provisions have the potential to benefit countries at all stages of development. It is estimated that a complete implementation of the trade facilitation measures arising from the WTO Agreement could reduce trade cost by 16.5% for low income countries, 17.4% for lower middle income countries, 14.6% for upper middle income countries, and 11.8% for OECD countries, boosting global growth and leading to significant welfare gains (Moïsé and Sorescu, 2013). UNCTAD (2016a) demonstrates a close statistical association not only between diverse trade facilitation measures and trade competitiveness, but also between trade facilitation implementation and broader development indicators.…”
Section: Implementing the Trade Facilitation Agreement For Cross-bordmentioning
confidence: 99%